RADIUS OF THE PERTURBATION OF THE OBJECTIVE FUNCTION PRESERVES THE KKT CONDITION IN CONVEX OPTIMIZATION - Ishibashi, K.; Kuroiwa, D. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2021)
The problem to find the maximum radius of the perturbation of the objective function which preserves the KKT condition at a feasible point is studied. The maximum radius of the problem is described, and certain values concerned with the extreme direction of a positive polar cone of the union of the subdifferentials of the active constraint functions at the point are observed.